Effect of light activation time and irradiance of multi-peak light curing unit on flowable and high viscosity bulk fill resin composites - Deus, Raissa Albuquerque de (2020)
The use of bulk fill resin composites to posterior restorations has increased in recent years. However, if resin composites receive less energy than required, they will be insufficiently polymerized and, consequently, have their properties impaired. Therefore, the light curing unit (LCU) is an essential part in the polymerization process of resin composites, and more studies about the interaction between light activation time, irradiance of LCU and characteristics of resin composites are necessary. The aim of this study was to evaluate the effect of light activation time and irradiance of multi-peak LCU on flowable and high viscosity bulk-fill resin composites though laboratory and computational tests. This study was sctutured into three specific objectives; objective 1: to evaluate the effect of light activation time (10, 20, 40s ) and irradiance (400, 800, 1200 mW/cm2)of multi-peak LCU on physical-mechanical properties expressed by radiopacity, degree of conversion, post-gel shrinkage, hardness and elastic modulus of bulk-fill resin composites; objective 2: to evaluate, by finite element analysis, the effect of the parameters recommended by manufacturers about light activation time for a LCU with 1200 mW/cm2; and also the effect of time (10, 20 and 40s) on the irradiance of 1200 mW/cm2 and the irradiance variation (400, 800 and 1200 mW/cm2) associated with 40s of light activation time in the generation of shrinkage stresses during the restoration and residual stresses during physiological occlusal loading (100N) in restored molars with different bulk fill resins; objective 3: to analyze the effect of the different irradiance and the real time light translucency on the light transmission of flowable and high viscosity bulk-fill resin composites. Five flowable bulk-fill resin composites (Tetric N-Flow Bulk Fill, Ivoclar Vivadent; Filtek Bulk Fill Flow, 3M Oral Care; Opus Bulk Fill Flow APS, FGM; Admira Fusion x-base, VOCO; e SureFil SDR Flow, Dentsply) and five high viscosity bulk-fill resin composites (Tetric N-Ceram Bulk Fill, Ivoclar Vivadent; Filtek One Bulk Fill, 3M Oral Care; Opus Bulk Fill APS, FGM; Admira Fusion x-tra, VOCO; e SonicFill 2, Kerr) were light cured, using VALO Cordless, varying the irradiances of 1200, 800 and 400 mW/cm2, according to distances of 1, 5 and 13 mm, respectively. The methods used on the all studies were post-gel measurements by strain gage test, degree of conversion using FTIR, indentation test for calculation of hardness Knoop and elastic modulus, digital radiographic to calculate radiopacity, finite element analysis 2D to evaluate shrinkage stresses and residual occlusal stress and a laser beam profiler camera to measure light beam profile of light transmitted. After data analysis it can be concluded that the irradiance level had more influence on mechanical properties than light activation time; the use of 1200 mW/cm2 with longer light activation time is a better strategy than the reduced light activation time recommender by some manufactures; the light activation time and irradiance had no influence on radiopacity for all tested resin composites; lower shrinkage and residual stresses were observed on molar tooth restored with flowable associated with high viscosity bulk fill resin composites; irradiance level influences the generation of shrinkage and residual stresses on molar teeth restored with different bulk fill resin composites more significantly than light activation time; the irradiance level affected the light transmission of bulk fill resin composites; flowable and high viscosity bulk fill resin composite had different light transmission after cured.